2004
DOI: 10.1007/s00438-004-1053-1
|View full text |Cite
|
Sign up to set email alerts
|

Nonsense mutations in the essential gene SUP35 of Saccharomyces cerevisiae are non-lethal

Abstract: In the present work we have characterized for the first time non-lethal nonsense mutations in the essential gene SUP35, which codes for the translation termination factor eRF3 in Saccharomyces cerevisiae. The screen used was based on selection for simultaneous suppression of two auxotrophic nonsense mutations. Among 48 mutants obtained, sixteen were distinguished by the production of a reduced amount of eRF3, suggesting the appearance of nonsense mutations. Fifteen of the total mutants were sequenced, and the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
52
1

Year Published

2005
2005
2015
2015

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 49 publications
(58 citation statements)
references
References 39 publications
2
52
1
Order By: Relevance
“…Similar nonlethal nonsense alleles of the eRF3 gene (SUP35) have also been identified in yeast (Chabelskaya et al 2004). The mutant SUP45 phenotypes exhibit increased nonsense suppression, which promote tRNA-mediated readthrough of the early stop codon and hence production of some reduced level of full-length release factor (Stansfield et al 1996).…”
Section: Introductionmentioning
confidence: 75%
“…Similar nonlethal nonsense alleles of the eRF3 gene (SUP35) have also been identified in yeast (Chabelskaya et al 2004). The mutant SUP45 phenotypes exhibit increased nonsense suppression, which promote tRNA-mediated readthrough of the early stop codon and hence production of some reduced level of full-length release factor (Stansfield et al 1996).…”
Section: Introductionmentioning
confidence: 75%
“…Of course, we cannot rule out the possibility that eRF3a forms containing mutations in the eRF1-binding site were misfolded and targeted to ubiquitin-proteasomedependent proteolysis. However, in yeast, eRF3 variants harboring C-terminal truncation that included the eRF1-binding site were expressed at almost the same level as that of wild-type eRF3, suggesting that these truncated proteins did not have increased sensitivity to proteolysis (Chabelskaya et al 2004). Moreover, we also observed polyubiquitinated forms of GFP-3a in MG132-treated cells, although at a lower level than that of GFP-3a-FRAA (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…Depletion of eRF3a, which is likely to be the main factor acting in translation termination, causes a significant reduction of 1 the eRF1 level by decreasing its stability (Chauvin et al 2005). In budding yeast, some reports showed that a reduced level of either eRF1 or eRF3 did not affect the level of its partner (Chabelskaya et al 2004;Salas-Marco and Bedwell 2004), whereas Valouev et al (2002) reported that depletion of either of the release factors is accompanied by a reduction in the level of the other.…”
Section: Introductionmentioning
confidence: 99%
“…A significant body of data is available regarding the translational fate of mRNA molecules containing nonsense mutations (Beier and Grimm 2001;Chabelskaya et al 2004;Doronina and Brown 2006;Lao et al 2009). These studies have revealed that a significant level of translational readthrough across stop codons occurs.…”
Section: Unassigned Codons and Nonsense Suppressionmentioning
confidence: 99%